Modulatory role of exopolysaccharides of Kluyveromyces marxianus and Pichia kudriavzevii as probiotic yeasts from dairy products in human colon cancer cells. (January 2020) - Rahbar Saadat, Yalda; Yari Khosroushahi, Ahmad; Movassaghpour, Ali Akbar; Talebi, Mehdi; Pourghassem Gargari, Bahram
Graphical abstract: Highlights: Employing new molecular based targeted therapies by non- saccharomyces probiotic strains in CRC. Targeting important molecular pathways via EPSs of K. marxianus and P. kudriavzevii . Targeting non-apoptotic forms of cell death besides the apoptotic cell death. Abstract: Colorectal cancer (CRC) is a widespread and lethal cancer throughout the world. Nowadays there is considerable debate about the efficacy of conventional methods in CRC treatment. Though targeting vital molecular pathways, as well as induction of various forms of cell death by safe probiotic yeast components are regarded as potential therapeutic modalities against CRC. Hence, here we aimed to investigate the inhibitory role of the EPSs of Kluyveromyces marxianus and Pichia kudriavzevii on different colon cancer cell lines. In this regard, several cellular and molecular experiments were performed. Here, we found that both EPSs can induce apoptosis which were confirmed by DAPI and Annexin V/PI assays. Further, our data showed that the EPSs could not act via ferroptotic pathways, however, they could hinder the AKT-1, mTOR, and JAK-1 pathways, and induce apoptosis. Therefore, the probiotic yeast EPSs present beneficial effects and may provide as a novel molecular-targeted therapeutics for combating CRC.